Genipin Cross-Linked Polymeric Alginate-Chitosan Microcapsules for Oral Delivery: In-Vitro Analysis - Hongmei Chen; Wei Ouyang; Christopher Martoni; Satya Prakash (International Journal of Polymer Science)
We have previously reported the preparation of the genipin cross-linked alginate-chitosan (GCAC) microcapsules composed of an alginate core with a genipin cross-linked chitosan membrane. This paper is the further investigation on their structural and physical characteristics. Results showed that the GCAC microcapsules had a smooth and dense surface and a networked interior. Cross-linking by genipin substantially reduced swelling and physical disintegration of microcapsules induced by nongelling ions and calcium sequestrants. Strong resistance to mechanical shear forces and enzymatic degradation was observed. Furthermore, the GCAC membranes were permeable to bovine serum albumin and maintained a molecular weight cutoff at 70 KD, analogous to the widely studied alginate-chitosan, and alginate-poly-L-lysine-alginate microcapsules. The release features and the tolerance of the GCAC microcapsules in the stimulated gastrointestinal environment were also investigated. This GCAC microcapsule formulation offers significant potential as a delivery vehicle for many biomedical applications.